Survey on RDMA protocol applications and security protection technologies - LIU Yumeng; TANG Zhengliang; LU Songfeng; ZHU Jianxin; LIU Yunqu (网络与信息安全学报)
The remote direct memory access (RDMA) technology, which has been effectively utilized to enhance data transfer rates and reduce CPU utilization, has played a significant role in various domains such as cross-regional data center transfers, high-performance computing, and rapid data read/write operations. However, despite its emerging status, RDMA has been lacking in widely recognized security solutions. With the expansion of RDMA applications from dedicated network environments to general Ethernet networks, the need to address the security risks faced by these applications has become imperative. A set of protective measures were established to ensure security without compromising transmission efficiency. Furthermore, the unique underlying implementation and protocol design of RDMA technology have resulted in incompatibility with existing mature security solutions and have led to the confrontation with specific security risks. The development of RDMA attack and defense technologies and the provision of security guarantees for the forthcoming widespread application of RDMA technology were elucidated The principles of RDMA technology and its implementation were proposed, with examples drawn from the InfiniBand (IB) and the RDMA over converged Ethernet (RoCE) second edition protocols. The security risks faced by RDMA applications in relevant scenarios were investigated, and a summary of the research progress in the RDMA security field over recent years was provided. Effective security solutions addressing these risks were compiled and, after their defensive capabilities were proven, a comparison of their advantages and disadvantages was conducted through theoretical analysis and experimental data. Finally, improvement plans and prospects for technological optimization in the RDMA attack and defense field were proposed.